Trade policy partial equilibrium model in Excel: Documentation - Laborde Debucquet, David; Tokgoz, Simla (International Food Policy Research Institute, 2013)
This is a partial equilibrium model for trade policy analysis (PE-TRADE) which is set up in Excel. The PE-TRADE model in Excel shows multiple examples of trade policy analyses with increasing details in each worksheet. In these examples, the focus is on the response of import demand to changes in trade policy and other tax policy instruments.